Prenehanje pogodbe o zaposlitvi z vidika standardov Mednarodne organizacije dela - Kresal, Barbara (Delavci in delodajalci, 2019)
The paper analyses various aspects of the international labour standards as regards termination of employment as developed by the ILO during its hundred years' existence and their impact on the legal regulation of termination of contract of employment. Special attention is given to the ILO Termination of Employment Convention No 158 from 1982 and its relevance in the context of the present and future changing patterns of labour relations, characterised among others by growing importance of the "new", non-standard forms of employment and precarisation of labour.
Keywords: dismissal; ILO convention No 158; konvencija MOD št. 158; nestandardne oblike zaposlitve; non-standard forms of employment; odpoved; precarious work; prekarno delo; prenehanje delovnega razmerja; prenehanje pogodbe o zaposlitvi; termination of contract of employment; termination of employment relationship